Evaluación de genotipos promisorios de cebada (Hordeum vulgare L.) en los Andes centrales de Perú - Llacsa, J. (2020)
The study was carried out in the central Andes of Peru aiming to evaluate promising genotypes of dual-purpose barley (greater grain and straw yield), cultivated during the dry season. Twenty-five genotypes, of which 22 were barley mutants generated by induction from the commercial variety UNA La Molina 96 were tested. A completely randomized block design with 25 barley genotypes and 3 replications per genotype was used. The yield in grain (kg/ha) and straw (kg DM/ha) was evaluated, as well as the protein content, neutral detergent fibre and in vitro digestibility of organic matter for the straw. The genotypes that showed the best characteristics for a dual-purpose barley were UNALM 96 M6h-617, followed by UNA 80 line 525 and UNALM 96 M6h-326. No significant relationship was found between grain and straw production.